Online Teaching and its challenges faced by Anatomists in Pakistan: A post-pandemic perspective - Inam, Fatima; Alvia Batool; Akhtar, Muhammad Shahid; Ahmed, Hafiza Sadia; Fariha Qureshi; Fauzia Qureshi (Journal of University Medical & Dental College, 2024)
BACKGROUND AND OBJECTIVE: Medical teachers in Pakistan lacked the concept of online teaching and had to adapt with limited resources and experience during the COVID-19 pandemic. They were also lacking the necessary IT skills and computer literacy. This study aims to access the different types of online teaching methods, explore computer literacy, and identify the challenges and opportunities faced by the teachers of anatomy to assess the success of online teaching. METHODOLOGY: An online survey gathered data from n=80, anatomy teachers on demographic factors, prior online teaching experience, teaching methods, IT skills, and perceptions of online teaching challenges and benefits. Responses were analyzed using frequencies and percentages. The Chi-square and Fisher’s exact tests were employed to explore relationships between dependent and independent variables. RESULTS: The study found that 17.5% of anatomy teachers had prior online teaching experience, with Zoom being the preferred app for 54% of respondents. A mix of synchronous and asynchronous teaching was favored by 48.75%. Most teachers reported IT skills above 70-80%. Teaching gross anatomy was cited as the biggest challenge by 74% of participants. Statistical analysis revealed no significant difference in app preference between junior and senior faculty (p > 0.05). CONCLUSION: Teachers of anatomy in Pakistan faced many difficulties in online teaching during the pandemic which is evident by this study conducted in post-pandemic time but did their best to deliver lectures using the resources available and minimal training.